Stochastic modelling for traffic flow: a review. (2017) - Borah, Kaustav Jyoti; Barbhuiya, Abul Abbas
The stochastic process and estimation from the review paper for the breakdown flow contains two random flow breakdowns variables. Breakdown flow happens when the two random variables, breakdown speed and breakdown duration, occurs at the homogeneous level. The model follows microscopic model which are homogeneous and continues in a heterogeneous level for a macroscopic model. The models are based from the vehicle changes at different levels of their speed. The mathematical process used in order to obtain the random variables are Weibull probability distribution for the breakdown speed and also the probability density function for the breakdown duration as an estimation also known as the hazard function. Simulation using Monte Carlo method will compute the random sampling from the breakdown variables and breakdown duration into a macroscopic model. The results will compare the actual data collected from Caltrans in 2007 and the mathematical model and simulation will be the same traffic flow behaviour and characteristics.